2020
DOI: 10.1002/ehf2.12837
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory signatures are associated with increased mortality after transfemoral transcatheter aortic valve implantation

Abstract: Aims Systemic inflammatory response, identified by increased total leucocyte counts, was shown to be a strong predictor of mortality after transcatheter aortic valve implantation (TAVI). Yet the mechanisms of inflammation-associated poor outcome after TAVI are unclear. Therefore, the present study aimed at investigating individual inflammatory signatures and functional heterogeneity of circulating myeloid and T-lymphocyte subsets and their impact on 1 year survival in a single-centre cohort of patients with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 48 publications
1
18
0
1
Order By: Relevance
“…Previous studies have reported that developing a systemic inflammatory response syndrome (SIRS) after transcatheter valve implantation (TAVI) is associated with poor prognosis [ 1 7 ]. In recent years, much effort has gone into improving existing prognostic models for risk stratification of patients undergoing TAVI.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that developing a systemic inflammatory response syndrome (SIRS) after transcatheter valve implantation (TAVI) is associated with poor prognosis [ 1 7 ]. In recent years, much effort has gone into improving existing prognostic models for risk stratification of patients undergoing TAVI.…”
Section: Introductionmentioning
confidence: 99%
“…SIRS was more frequent in patients with adverse short-term outcome and was independently associated with long-term mortality. Previous studies reported a variable prevalence of SIRS after TAVI ranging from 10 to 73% 4,5,12–15 . Several possible mechanisms can concur to cause SIRS.…”
Section: Discussionmentioning
confidence: 98%
“…A recent subgroup analysis of the CANTOS (Canakinumab Anti-inflammatory Thrombosis Outcome Study) trial showed that IL-1β-targeting therapy may decrease heart failure-related hospitalization and mortality ( 38 ). Lately, a proof-of-concept study, showed, for the first time, an association of specific inflammatory phenotypes (immune signatures) with increased mortality after TAVI ( 39 ). Thus, suggesting that distinct monocyte and T-cell signatures might stand as novel biomarkers to be considered in risk stratifying patients with severe aortic stenosis undergoing TAVI, and possibly guiding potential anti-inflammatory treatment.…”
Section: Discussionmentioning
confidence: 99%